2022
DOI: 10.1101/2022.03.10.22271805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 seroconversion in response to infection and vaccination: A time series local study in Brazil

Abstract: The investigation of antibodies raised against different SARS-CoV-2 antigens can help to determine the extent of previous SARS-CoV-2 infections in the population and track the humoral response to vaccination. Therefore, serological surveys can provide key information to better manage the pandemic and/or to implement the most effective vaccination program. Here we describe a time series anti-Nucleocapsid, anti-Spike IgG serological survey analysis in the city of Matinhos, PR, Brazil during the year of 2021. Ser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Compared to surveys conducted in Brazil around mid-2021 the seroprevalence of antibodies against SARS-CoV-2 in our sample (53.61%) was higher than other studies reported in the South and Southeast regions of Brazil ( 14 , 16 , 17 ), being closer to rates observed at that time in the North region ( 18 , 19 ) and in indigenous populations ( 20 , 21 ). With a vaccine coverage of 37% in our study population, the large difference in seroprevalence between vaccinated (90.5%) and unvaccinated (31%) residents confirmed findings from other studies ( 22 ) of how vaccination decisively contributes to the population's immunity, even in an area with a high prevalence of infection-induced antibodies after exposure to a pandemic for more than a year.…”
Section: Discussioncontrasting
confidence: 71%
“…Compared to surveys conducted in Brazil around mid-2021 the seroprevalence of antibodies against SARS-CoV-2 in our sample (53.61%) was higher than other studies reported in the South and Southeast regions of Brazil ( 14 , 16 , 17 ), being closer to rates observed at that time in the North region ( 18 , 19 ) and in indigenous populations ( 20 , 21 ). With a vaccine coverage of 37% in our study population, the large difference in seroprevalence between vaccinated (90.5%) and unvaccinated (31%) residents confirmed findings from other studies ( 22 ) of how vaccination decisively contributes to the population's immunity, even in an area with a high prevalence of infection-induced antibodies after exposure to a pandemic for more than a year.…”
Section: Discussioncontrasting
confidence: 71%